Coordinate Regulation of the Escherichia coli Formate Dehydrogenase fdnGHI and fdhF Genes in Response to Nitrate, Nitrite, and Formate: Roles for NarL and NarP - Wang, Henian (American Society for Microbiology, 2003)
Escherichia coli possesses three distinct formate dehydrogenase enzymes encoded by the fdnGHI, fdhF, and fdoGHI operons. To examine how two of the formate dehyrogenase operons (fdnGHI and fdhF) are expressed anaerobically in the presence of low, intermediate, and high levels of nitrate, nitrite, and formate, chemostat culture techniques were employed with fdnG-lacZ and fdhF-lacZ reporter fusions. Complementary patterns of gene expression were seen. Optimal fdhF-lacZ expression occurred only at low to intermediate levels of nitrate, while high nitrate levels caused up to 10-fold inhibition of gene expression. In contrast, fdnG-lacZ expression was induced 25-fold in the presence of intermediate to high nitrate concentrations. Consistent with prior reports, NarL was able to induce fdnG-lacZ expression. However, NarP could not induce expression; rather, it functioned as an antagonist of fdnG-lacZ expression under low-nitrate conditions (i.e., it was a negative regulator). Nitrite, a reported signal for the Nar sensory system, was unable to stimulate or suppress expression of either formate dehydrogenase operon via NarL and NarP. The different gene expression profiles of the alternative formate dehydrogenase operons suggest that the two enzymes have complementary physiological roles under environmental conditions when nitrate and formate levels are changing. Revised regulatory schemes for NarL- and NarP-dependent nitrate control are presented for each operon.